Transient and sustained processing of musical consonance in auditory cortex and the effect of musicality - Andermann, Martin; Patterson, Roy D.; Rupp, André (Journal of neurophysiology, 2020)
In recent years, electroencephalography and magnetoencephalography (MEG) have both been used to investigate the response in human auditory cortex to musical sounds that are perceived as consonant or dissonant. These studies have typically focused on the transient components of the physiological activity at sound onset, specifically, the N1 wave of the auditory evoked potential and the auditory evoked field, respectively. Unfortunately, the morphology of the N1 wave is confounded by the prominent neural response to energy onset at stimulus onset. It is also the case that the perception of pitch is not limited to sound onset; the perception lasts as long as the note producing it. This suggests that consonance studies should also consider the sustained activity that appears after the transient components die away. The current MEG study shows how energy-balanced sounds can focus the response waves on the consonance-dissonance distinction rather than energy changes and how source modeling techniques can be used to measure the sustained field associated with extended consonant and dissonant sounds. The study shows that musical dyads evoke distinct transient and sustained neuromagnetic responses in auditory cortex. The form of the response depends on both whether the dyads are consonant or dissonant and whether the listeners are musical or nonmusical. The results also show that auditory cortex requires more time for the early transient processing of dissonant dyads than it does for consonant dyads and that the continuous representation of temporal regularity in auditory cortex might be modulated by processes beyond auditory cortex. NEW & NOTEWORTHY We report a magnetoencephalography (MEG) study on transient and sustained cortical consonance processing. Stimuli were long-duration, energy-balanced, musical dyads that were either consonant or dissonant. Spatiotemporal source analysis revealed specific transient and sustained neuromagnetic activity in response to the dyads; in particular, the morphology of the responses was shaped by the dyad's consonance and the listener's musicality. Our results also suggest that the sustained representation of stimulus regularity might be modulated by processes beyond auditory cortex.